Training Model of Coordination for Pencak Silat Athletes aged 13-16 Years - Eka Ardiana; Ramdan Pelana; Widiastuti , Widiastuti; Fahmy Fachrezzy; Oman U. Subandi (UNIB Press, 2024)
This research was motivated by the lack of coordination of movements in pencak silat athletes aged 13-16 years. The aim of this research is to produce a product and determine the effectiveness of coordination training through a coordination training model for Pencak Silat athletes aged 13-16 years. The research and development model is the ADDIE model. The subjects of this research were pencak silat athletes aged 13-16 years at the Terate Jaya Sasana Club and Batavia Silat Padepokan Pencak Silat Indonesia. This research was conducted from March to June 2024. The results of the research findings using the paired sample t test obtained a t count of 9.277 with a p-value of 0.000 <0.05, meaning that the coordination training model can be applied. Thus, it is concluded that there is a significant difference before and after receiving treatment through the coordination training model to improve coordination for pencak silat athletes aged 13-16 years.